Mechanical stability of bivalent transition metal complexes analyzed by single-molecule force spectroscopy - Gensler, Manuel; Eidamshaus, Christian; Taszarek, Maurice; Reissig, Hans-Ulrich; Rabe, Jürgen P. (Beilstein Journal of Organic Chemistry, 2015)
Multivalent biomolecular interactions allow for a balanced interplay of mechanical stability and malleability, and nature makes widely use of it. For instance, systems of similar thermal stability may have very different rupture forces. Thus it is of paramount interest to study and understand the mechanical properties of multivalent systems through well-characterized model systems. We analyzed the rupture behavior of three different bivalent pyridine coordination complexes with Cu2+ in aqueous environment by single-molecule force spectroscopy. Those complexes share the same supramolecular interaction leading to similar thermal off-rates in the range of 0.09 and 0.36 s−1, compared to 1.7 s−1 for the monovalent complex. On the other hand, the backbones exhibit different flexibility, and we determined a broad range of rupture lengths between 0.3 and 1.1 nm, with higher most-probable rupture forces for the stiffer backbones. Interestingly, the medium-flexible connection has the highest rupture forces, whereas the ligands with highest and lowest rigidity seem to be prone to consecutive bond rupture. The presented approach allows separating bond and backbone effects in multivalent model systems.
Keywords: molecular rupture mechanism; multivalency; malleability; pyridine coordination compounds; scanning force microscopy

(untitled) - Kiessling, L. L.; Gestwicki, J. E.; Strong, L. E. (Angew. Chem., Int. Ed., 2006)

(untitled) - Badjić, J. D.; Nelson, A.; Cantrill, S. J.; Turnbull, W. B.; Stoddart, J. F. (Acc. Chem. Res., 2005)

(untitled) - Fasting, C.; Schalley, C. A.; Weber, M.; Seitz, O.; Hecht, S.; Koksch, B.; Dernedde, J.; Graf, C.; Knapp, E.-W.; Haag, R. (Angew. Chem., Int. Ed., 2012)

(untitled) - Mulder, A.; Huskens, J.; Reinhoudt, D. N. (Org. Biomol. Chem., 2004)

(untitled) - Diestler, D. J.; Knapp, E. W. (J. Phys. Chem. C, 2010)

(untitled) - Hoffmann, T.; Tych, K. M.; Hughes, M. L.; Brockwell, D. J.; Dougan, L. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Woelke, A. L.; Kuehne, C.; Meyer, T.; Galstyan, G.; Dernedde, J.; Knapp, E.-W. (J. Phys. Chem. B, 2013)

(untitled) - Mu, X.-Q.; Jiang, Z. G.; Bullitt, E. (J. Mol. Biol., 2005)

(untitled) - Lugmaier, R. A.; Schedin, S.; Kühner, F.; Benoit, M. (Eur. Biophys. J., 2008)

(untitled) - Schoeler, C.; Malinowska, K. H.; Bernardi, R. C.; Milles, L. F.; Jobst, M. A.; Durner, E.; Ott, W.; Fried, D. B.; Bayer, E. A.; Schulten, K.; Gaub, H. E.; Nash, M. A. (Nat. Commun., 2014)

(untitled) - Zhang, X.; Halvorsen, K.; Zhang, C.-Z.; Wong, W. P.; Springer, T. A. (Science, 2009)

(untitled) - Li, H.; Linke, W. A.; Oberhauser, A. F.; Carrion-Vazquez, M.; Kerkvliet, J. G.; Lu, H.; Marszalek, P. E.; Fernandez, J. M. (Nature, 2002)

(untitled) - Lv, S.; Dudek, D. M.; Cao, Y.; Balamurali, M. M.; Gosline, J.; Li, H. (Nature, 2010)

(untitled) - Groote, R.; Jakobs, R. T. M.; Sijbesma, R. P. (Polym. Chem., 2013)

(untitled) - Dietz, H.; Berkemeier, F.; Bertz, M.; Rief, M. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Bertz, M.; Wilmanns, M.; Rief, M. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Rief, M.; Pascual, J.; Saraste, M.; Gaub, H. E. (J. Mol. Biol., 1999)

(untitled) - Li, M. S. (Biophys. J., 2007)

(untitled) - Sikora, M.; Sulkowska, J. I.; Witkowski, B. S.; Cieplak, M. (Nucleic Acids Res., 2011)

(untitled) - Kramers, H. A. (Physica, 1940)

(untitled) - Bell, G. I. (Science, 1978)

(untitled) - Evans, E. (Annu. Rev. Biophys. Biomol. Struct., 2001)

(untitled) - Wollschläger, K.; Gaus, K.; Körnig, A.; Eckel, R.; Wilking, S.-D.; McIntosh, M.; Majer, Z.; Becker, A.; Ros, R.; Anselmetti, D.; Sewald, N. (Small, 2009)

(untitled) - Zocher, M.; Zhang, C.; Rasmussen, S. G. F.; Kobilka, B. K.; Müller, D. J. (Proc. Natl. Acad. Sci. U. S. A., 2012)

(untitled) - Kawamura, S.; Colozo, A. T.; Ge, L.; Müller, D. J.; Park, P. S.-H. (J. Biol. Chem., 2012)

(untitled) - Kudera, M.; Eschbaumer, C.; Gaub, H. E.; Schubert, U. S. (Adv. Funct. Mater., 2003)

(untitled) - Gensler, M.; Eidamshaus, C.; Galstyan, A.; Knapp, E.-W.; Reissig, H.-U.; Rabe, J. P. (J. Phys. Chem. C, 2015)

(untitled) - Kersey, F. R.; Yount, W. C.; Craig, S. L. (J. Am. Chem. Soc., 2006)

(untitled) - Schönherr, H.; Beulen, M. W. J.; Bügler, J.; Huskens, J.; van Veggel, F. C. J. M.; Reinhoudt, D. N.; Vancso, G. J. (J. Am. Chem. Soc., 2000)

(untitled) - Eckel, R.; Ros, R.; Decker, B.; Mattay, J.; Anselmetti, D. (Angew. Chem., Int. Ed., 2005)

(untitled) - Schröder, T.; Geisler, T.; Walhorn, V.; Schnatwinkel, B.; Anselmetti, D.; Mattay, J. (Phys. Chem. Chem. Phys., 2010)

(untitled) - Walhorn, V.; Schäfer, C.; Schröder, T.; Mattay, J.; Anselmetti, D. (Nanoscale, 2011)

(untitled) - Lussis, P.; Svaldo-Lanero, T.; Bertocco, A.; Fustin, C.-A.; Leigh, D. A.; Duwez, A.-S. (Nat. Nanotechnol., 2011)

(untitled) - Guzmán, D. L.; Roland, J. T.; Keer, H.; Kong, Y. P.; Ritz, T.; Yee, A.; Guan, Z. (Polymer, 2008)

(untitled) - Beijer, F. H.; Kooijman, H.; Spek, A. L.; Sijbesma, R. P.; Meijer, E. W. (Angew. Chem., Int. Ed., 1998)

(untitled) - Embrechts, A.; Velders, A. H.; Schönherr, H.; Vancso, G. J. (Langmuir, 2011)

(untitled) - Zhang, Y.; Yu, Y.; Jiang, Z.; Xu, H.; Wang, Z.; Zhang, X.; Oda, M.; Ishizuka, T.; Jiang, D.; Chi, L.; Fuchs, H. (Langmuir, 2009)

(untitled) - Grandbois, M.; Beyer, M.; Rief, M.; Clausen-Schaumann, H.; Gaub, H. E. (Science, 1999)

(untitled) - Krüger, D.; Fuchs, H.; Rousseau, R.; Marx, D.; Parrinello, M. (Phys. Rev. Lett., 2002)

(untitled) - Heymann, B.; Grubmüller, H. (Chem. Phys. Lett., 1999)

(untitled) - Oesterhelt, F.; Rief, M.; Gaub, H. E. (New J. Phys., 1999)

(untitled) - Noy, A. (Curr. Opin. Chem. Biol., 2011)

(untitled) - Ray, C.; Brown, J. R.; Kirkpatrick, A.; Akhremitchev, B. B. (J. Am. Chem. Soc., 2008)

(untitled) - Friedsam, C.; Wehle, A. K.; Kühner, F.; Gaub, H. E. (J. Phys.: Condens. Matter, 2003)

(untitled) - Merkel, R.; Nassoy, P.; Leung, A.; Ritchie, K.; Evans, E. (Nature, 1999)

(untitled) - Dudko, O.; Hummer, G.; Szabo, A. (Phys. Rev. Lett., 2006)

(untitled) - Raible, M.; Evstigneev, M.; Bartels, F. W.; Eckel, R.; Nguyen-Duong, M.; Merkel, R.; Ros, R.; Anselmetti, D.; Reimann, P. (Biophys. J., 2006)

(untitled) - Schmidt, S. W.; Pill, M. F.; Kersch, A.; Clausen-Schaumann, H.; Beyer, M. K. (Faraday Discuss., 2014)

(untitled) - Schmidt, S. W.; Kersch, A.; Beyer, M. K.; Clausen-Schaumann, H. (Phys. Chem. Chem. Phys., 2011)

(untitled) - Hohenstein, E. G.; Sherrill, C. D. (J. Phys. Chem. A, 2009)

(untitled) - Hegner, M.; Wagner, P.; Semenza, G. (Surf. Sci., 1993)

(untitled) - Wagner, P.; Hegner, M.; Guentherodt, H.-J.; Semenza, G. (Langmuir, 1995)

(untitled) - Vig, J. R. (J. Vac. Sci. Technol., A, 1985)

(untitled) - Struckmeier, J.; Wahl, R.; Leuschner, M.; Nunes, J.; Janovjak, H.; Geisler, U.; Hofmann, G.; Jähnke, T.; Müller, D. J. (Nanotechnology, 2008)

(untitled) - Hutter, J. L.; Bechhoefer, J. (Rev. Sci. Instrum., 1993)

(untitled) - Sandal, M.; Benedetti, F.; Brucale, M.; Gomez-Casado, A.; Samorì, B. (Bioinformatics, 2009)